INTERAKTIF PEMBUATAN POLA DASAR BUSANA WANITA - Nur Saadah Inten P; Cucu Ruhidawati (Fesyen Perspektif, 2016)
Based on preliminary study on Construction of Clothing Pattern by students of Fashion Education, media which have been used in basic pattern making of women’s wear currently are still limited to the use of blackboard and job sheet. This study was aimed to make multimedia design of interactive learning, to get the validation results from subject expert and multimedia expert as well as the analysis of validation results. The multimedia made was multimedia of interactive learning on basic pattern making with So-En system. The method used in this study was Research and Development (RD) method through the phases of analysis, design, development, validation, revision and evaluation. The validation results showed that multimedia expert and subject expert agreed that multimedia of interactive learning made was eligible to use.